The Influence of Logical Intelligence of Mathematics and Soft Skills on Students’ Learning Outcomes of Introductory Economics Course - Thamrin Thamrin; Abdul Hasan Saragih; Abdul Muin Sibuea (BIRCU, 2019)
The problem of education is relatively complex because many variables influence it. One of these factors is the characteristics (logical intelligence mathematics) and student Soft Skills. The phenomena that occur in the field, especially in the learning process of the lecturer/teacher, that they do not pay attention to the problems of logical intelligence of mathematics and student soft skills, so that the learning outcomes are not optimal. This study aims to determine the effect of logical intelligence of mathematics and soft skills on learning outcomes in students of introductory economics. This research method is the descriptive ex-post facto method. The population in this study were all students of the economic education department in Economics Faculty Unimed who were attending the introductory economics as many as 90 people. The data collected was analyzed using linear regression statistics with SPSS for windows. The results of this study indicate that logical intelligence of mathematics and soft skills have a positive and significant effect on student outcomes in the introductory economics course.